2007
DOI: 10.1063/1.2734870
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring energy and cell gap effects on liquid crystal response time

Abstract: Anchoring energy enhancement and pretilt angle control of liquid crystal alignment on polymerized surfaces AIP Advances 5, 097218 (2015);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
104
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(110 citation statements)
references
References 15 publications
5
104
0
1
Order By: Relevance
“…We measured a s off of 0.65 ms, almost field-independent (0.62 ms at 5 V), and a clearly shorter s on from 1 ms (5 V) to 0.34 ms (10 V), directly related to the increase of the torque imposed by the increased external field. 39 As previously mentioned, the LC molecules can be subjected to pinning effects at the transition from homeotropic to planar alignment domains (see Figure 5). At the edges between these two domains, in fact, the nematic director tries to find an equilibrium, in which the Frank elasticity enforces the inhomogeneity near the edge to relax into the uniform bulk orientation over a characteristic length of the order of the pattern size, as schematically represented in Figure 5.…”
Section: Resultsmentioning
confidence: 97%
“…We measured a s off of 0.65 ms, almost field-independent (0.62 ms at 5 V), and a clearly shorter s on from 1 ms (5 V) to 0.34 ms (10 V), directly related to the increase of the torque imposed by the increased external field. 39 As previously mentioned, the LC molecules can be subjected to pinning effects at the transition from homeotropic to planar alignment domains (see Figure 5). At the edges between these two domains, in fact, the nematic director tries to find an equilibrium, in which the Frank elasticity enforces the inhomogeneity near the edge to relax into the uniform bulk orientation over a characteristic length of the order of the pattern size, as schematically represented in Figure 5.…”
Section: Resultsmentioning
confidence: 97%
“…The response times were within the range of a few tens of milliseconds. The rise time in the weak surface anchoring condition decreases along with the anchoring energy according to the relationship between the rise time (τ r ) and the polar anchoring energy (W), which can be obtained through the effective cell gap method, as follows [8]:…”
Section: Resultsmentioning
confidence: 99%
“…In the 0-2.5 wt% RM concentration range, the threshold voltage decreased to 2.32 V (from about 2.80 V for the unexposed case with no RM), whereas at above 5.0 wt% it increased monotonically with increasing RM concentration. The relationship between the threshold voltage (V th ) and the polar anchoring energy (W), obtained using the effective cell gap method [8,15], is written as follows:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The homeotropically aligned LCs have been extensively used for LC displays ͑LCDs͒ such as large-area LCD televisions, information display devices, and digital displays in medical devices due to its unprecedented contrast ratio and wide viewing angle characteristics. 1 The various techniques have been investigated to accomplish the homeotropic ͑HMT͒ alignment of LCs by the researchers around the world. [2][3][4][5][6][7][8] It has been observed that the minute addition of nanomaterials ͑e.g., nanoparticles, nanotubes, etc.͒ to LC materials has improved many special characteristics in the form of frequency modulation response, 9 nonvolatile memory effect, 10 faster electro-optic response and low threshold switching, 11,12 low driving voltage, 13 enhanced photoluminescence, 14 and reduced residual dc.…”
Section: Introductionmentioning
confidence: 99%